2015
DOI: 10.1186/s12957-014-0417-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of defunctioning stoma in low anterior resection with total mesorectal excision for rectal cancer: evidence based on thirteen studies

Abstract: BackgroundRecent studies have shown that a protective stoma can reduce morbidity in low anterior resection for rectal cancer; however, the necessity of it is still controversially discussed.MethodsWe performed this meta-analysis to provide a comprehensive evaluation of the role of defunctioning stoma in low anterior resection for rectal cancer on the rates of anastomotic leakage and reoperation related to leakage with or without defunctioning stoma by calculating the pooled risk ratio.ResultsStudies and releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 36 publications
(26 reference statements)
1
61
0
5
Order By: Relevance
“…Protective stoma prevents ALs and additionally, some leaks can remain asymptomatic [27]. In our study, we did not perform CT scans routinely in all patients; therefore, we were not able to diagnose the latter group of AL.…”
Section: Discussionmentioning
confidence: 81%
“…Protective stoma prevents ALs and additionally, some leaks can remain asymptomatic [27]. In our study, we did not perform CT scans routinely in all patients; therefore, we were not able to diagnose the latter group of AL.…”
Section: Discussionmentioning
confidence: 81%
“…The recommended average ostomy closure interval is around 3 months. Patients who have severe surgical complications, fistula occurrence, or high risk factors for local recurrence should not have their ostomy reconstructed for intestinal transit re‐establishment …”
Section: Resultsmentioning
confidence: 99%
“…Several studies in the past have found that the rate of anastomotic leakage was not reduced by the construction of defunctioning proximal stoma [11, 13, and 18]. However, couple of recent meta-analyses have shown that defunctioning proximal stoma significantly reduces the incidence as well as the consequences of the anastomotic leakage [19,20]. In this study, rates of anastomotic leakage were higher when defunctioning proximal stoma was not constructed (14.9 % vs 6.2 %) though it did not reach statistical significance (p = 0.068).…”
Section: Discussionmentioning
confidence: 99%